`a,x^2 -4x+3`
`=x^2 -x-3x+3`
`=x(x-1)-3(x-1)`
`=(x-1)(x-3)`
`b,x^2 +5x+4`
`=x^2 +x+4x+4`
`=x(x+1)+4(x+1)`
`=(x+1)(x+4)`
`a)`
\(x^2-4x+3\\ =x^2-x-3x+3\\ =x\left(x-1\right)-3\left(x-1\right)\\ =\left(x-3\right)\left(x-1\right)\)
`b)`
\(x^2+5x+4\\ =x^2+x+4x+4\\ =x\left(x+1\right)+4\left(x+1\right)\\ =\left(x+4\right)\left(x+1\right)\)
a) x2 - 4x + 3 = x2 - x - 3x + 3 = x(x - 1) - 3(x - 1) = (x - 1)(x - 3)
b) x2 + 5x + 4 = x2 + x + 4x + 4 = x(x + 1) + 4(x + 1) = (x + 1)(x + 4)
\(=x^2-x-3x+3\)
\(=x(x-1)-3(x-1)\)
\(=(x-1)(x-3)\)
\(-----------------\)
\(=x^2+x+4x+4\)
\(=x(x+1)+4(x+1)\)
\(=(x+1)(x+4)\)